The plethora of Tubeufiaceae in lakes of the northwestern Yunnan plateau, China - Li, Long-Li; Shen, Hong-Wei; Bao, Dan-Feng; Wanasinghe, Dhanushka N.; Lu, Yong-Zhong; Feng, Yuan; Luo, Zong-Long (Frontiers in Microbiology, 2022)
The diversity of lignicolous freshwater fungi in northwestern Yunnan, China, has been studied for several years in the College of Agriculture and Biological Science, at Dali University. Over the last 5 years, we published two new genera and nine new species of Tubeufiaceae from northwestern Yunnan. This study focused on introducing tubeufia-like hyphomycetous fungi found in freshwater lakes in the northwestern Yunnan plateau. Eleven fresh collections of tubeufiaceous taxa were gathered and identified. Among them, a new genus, Neomanoharachariella, is introduced to accommodate Neomanoharachariella aquatica, which is characterized by a light brown to dark brown color, dictyoseptate, and broadly oval to ellipsoid and well-developed conidiophores. Two new species, viz., Neohelicosporium suae and Parahelicomyces suae, one new record, Helicoma rufum, and three new collections, namely, H. rugosum, P. hyalosporus, and Tubeufia cylindrothecia are introduced based on morphological evidence and molecular phylogenetic analysis of combined ITS, LSU, tef 1-α, and RPB2 sequence data. Detailed descriptions and illustrations of these species are provided, and a morphological comparison with similar taxa is discussed.